2015
DOI: 10.1007/s00415-015-7798-0
|View full text |Cite
|
Sign up to set email alerts
|

Treating relapsing–remitting multiple sclerosis: therapy effects on brain atrophy

Abstract: Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system with a complex and heterogeneous pathology that may ultimately lead to neurodegeneration and brain atrophy. Brain volume loss in MS is known to occur early in the disease course and to be clinically relevant, as it has been related to disability progression. Nowadays, brain volume loss is relatively easy to measure with different automated, reproducible and accurate software tools. Therefore, most of (if not all) the newest cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 71 publications
(113 reference statements)
1
33
0
Order By: Relevance
“…It has been shown that current DMTs can reduce focal inflammatory activity as well as the accumulation of disability6 and the rate of brain atrophy 7. The currently available DMTs differ in respect to treatment efficacy and associated risks, stressing the importance of clinical tools to individualize the choice of DMT and closely monitor the treatment efficacy 6.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that current DMTs can reduce focal inflammatory activity as well as the accumulation of disability6 and the rate of brain atrophy 7. The currently available DMTs differ in respect to treatment efficacy and associated risks, stressing the importance of clinical tools to individualize the choice of DMT and closely monitor the treatment efficacy 6.…”
Section: Introductionmentioning
confidence: 99%
“…Brain atrophy has become increasingly important due to its core role in the pathophysiology of MS, correlations with clinical dysfunction, and the technological post-processing advances allowing a continuing increase in the sophistication of MRI quantification methods [1, 519]. In addition, the use of higher-field (i.e., 3T) MRI scanners provides the potential for increased accuracy and reliability in the assessment of lesions and atrophy [9, 10, 20].…”
Section: Introductionmentioning
confidence: 99%
“…55 The more recent DMTs have been shown to decrease rates of brain atrophy when compared with a placebo. 72 Thus, recent clinical trials have incorporated BV outcomes as a measure of treatment effect. 73 Current methods for measuring BV in radiology are usually automated software that either uses a segmentation-based approach (such as statistical parametric mapping) for cross-sectional data or a registration-based approach (such as structural image evaluation with normalization of atrophy) for longitudinal analysis.…”
Section: Future Areasmentioning
confidence: 99%
“…73 Current methods for measuring BV in radiology are usually automated software that either uses a segmentation-based approach (such as statistical parametric mapping) for cross-sectional data or a registration-based approach (such as structural image evaluation with normalization of atrophy) for longitudinal analysis. 72 Unfortunately, the clinical interpretation of BV loss in patients with MS can often be difficult with other confounding factors such as hydration status and ongoing inflammation at the time of treatment onset. 74 Moreover, differences in the quality and capabilities of MR imaging hardware and in the software packages used for analysis or processing can generate notable variability in brain atrophy assessment.…”
Section: Future Areasmentioning
confidence: 99%